2020
DOI: 10.4014/jmb.1909.09041
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Displayed Porcine IFN-λ3 in Lactobacillus plantarum Inhibits Porcine Enteric Coronavirus Infection of Porcine Intestinal Epithelial Cells

Abstract: Interferon (IFN)-λ plays an essential role in mucosal cells which exhibit strong antiviral activity.Lactobacillus plantarum (L. plantarum) has substantial application potential in the food and medical industries because of its probiotic properties. Alphacoronaviruses, especially porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV), cause high morbidity and mortality in piglets resulting in economic loss. Co-infection by these two viruses is becoming increasingly frequent. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Lactobacillus casei oral vaccine could induce the production of IgG (systemic) and SIgA antibody (mucosal) in a murine model [196]. Several other studies have employed various probiotics to present PEDV genes or antigens of interest [111,114,196,197]. Liu et al [111] showed that an altered Lactobacillus plantarum strain had antiviral activity against coronavirus infections in a porcine intestinal epithelial cell line.…”
Section: The Potential Effects Of Probiotics On Coronavirus Infectionmentioning
confidence: 99%
“…Lactobacillus casei oral vaccine could induce the production of IgG (systemic) and SIgA antibody (mucosal) in a murine model [196]. Several other studies have employed various probiotics to present PEDV genes or antigens of interest [111,114,196,197]. Liu et al [111] showed that an altered Lactobacillus plantarum strain had antiviral activity against coronavirus infections in a porcine intestinal epithelial cell line.…”
Section: The Potential Effects Of Probiotics On Coronavirus Infectionmentioning
confidence: 99%
“…Evidence for antiviral activity of probiotic strains against common respiratory viruses, including influenza, rhinovirus, and respiratory syncytial virus comes from clinical and experimental studies (17)(18)(19)41). While none of these effects or mechanisms have been tested on the new SARS-CoV-2 virus, this should not negate considering this approach, especially when effects of probiotics against other coronavirus strains have been reported (42)(43)(44)(45). Furthermore, patients are dying from secondary bacterial infections.…”
Section: Mechanistic Basis For the Action Of Probiotics To Prevent Inmentioning
confidence: 99%
“…Probiotics and recombinant probiotics with antiviral effects are effectively used to combat and minimize the detrimental effects of other coronaviruses, such as alphacoronavirusesparticularly transmissible gastroenteritis virus (TGEV) and porcine epidemic diarrhea virus (PEDV)-which cause substantial economic losses in the pork meat industry. Recombinant L. plantarum inhibits TGEV and PEDV infections in the IPEC-J2 cell line by enhancing ISGs (OASL, ISG15, and Mx1) which have strong antiviral effects (199). Recombinant L. plantarum (containing the surface S antigen of TGEV) elicits an immune response characterized by higher numbers of activated DC cells, B + IgA + cells, secretory IgA (sIgA), serum IgG, IFN-γ, and IL4 which help the host to combat TGEV (200).…”
Section: Coronavirusmentioning
confidence: 99%